Reliability and validity of the Chinese version of the Athletes’ Received Support Questionnaire - Yilin, Ren; Kequn, Chu; Fengshu, Zhu (Frontiers in Psychology, 2023)
Objective The aim of this study was to translate the Athletes’ Received Support Questionnaire (ARSQ) for Chinese athletes and examine the reliability and validity of the ARSQ with Chinese subjects. Methods In this study, we conducted a forward-backward translation of the ARSQ and used data collected from Chinese athletes to perform exploratory and confirmatory factor analyses. A total of 580 Chinese athletes completed the formal ARSQ for the confirmatory factor analysis (CFA), while 230 athletes participated in the preliminary survey. Of the 580 athletes, 571 provided valid questionnaires for assessing validity and reliability. Additionally, we assessed test–retest reliability using data from 200 participants randomly selected after 1 month. The criterion measurement used in this study was the Social Support Rate Scale (SSRS). Results Results of the exploratory factor analysis showed that the Chinese version of the ARSQ with 22 items had four-dimensional structures including emotional support, esteem support, information support, and tangible support. CFA showed that the Chinese version of the ARSQ had adequate structural validity (χ2/df = 2.315, CFI = 0.971, GFI = 0.902, NFI = 0.959, AGFI = 0.878, RMSEA = 0.064, SRMR = 0.032). Cronbach’s α coefficient, McDonald’s omega coefficient and the test–retest reliability were 0.956, 0.957, and 0.953 for the total scale. Conclusion The study provides evidence in support of construct (factorial) validity, convergent validity, internal-consistency and test–retest stability for the use of the ARSQ among Chinese athletes in the Jiangsu and Shandong Provinces, China. However, it is important to note that the conclusion is delimited to the current context, and further studies are needed to verify and promote the applicability of the ARSQ in other regions and sports projects.